Hubungan Pengetahuan, Sikap dengan Tindakan Pencegahan HIV/AIDS pada Siswa SMA Manado International School - Tampi, David; Kandou, Grace D.; Ratag, Gustaaf E.A. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2013)
HIV/AIDS are the most destructive pandemic in the history, it kills more than 25 million people since found in 1981.At the end of the year 2007, estimated 33,2 (30,6-36,1) million adults and kids lives with HIV world wide. In the earlyof 1981 United States of America reported that this infectious disease spread through out unsafe sexual intercourseand constantly changing in sexual partner. In 1982-1983 they found that this infectious disease transmitted not onlyby unsafe sexual intercourse and constantly changing in sexual partner but also through blood transfusions injectionamong injecting drug users together by IUDs. In North Sulawesi there has been 18 cases and 9 death cases in 1991 to2010. In North Sulawesi there is at least 275 people that are infected with HIV and 483 people that are positive withAIDS. Over all total of people that are infected by this deadly transmitted infectious disease are around 758 people andit could increase over time because of the people’s adapting the Heterosexual behavior which is constantly changingin sexual partner and by using blood transfusions injection among injecting drug users together by IUDs. The mainpurpose of this research is to measure the knowledge level and how the high school students react on preventing theHIV/AIDS spread in Manado International School. This research are using Cross-Sectional method. Sample of this researchare taken in Manado International School grade 10 and 11 of high school stundents. The results of this researchshows that some of the respondent knowledge were good on how to prevent HIV/AIDS with 84 respondent (70%)and some of respondent attitude shows a positive sign on how to prevent this viruses with 77 respondent (64,2%0.The advice that can be given is that the students were able to open their mind on how deadly this HIV/AIDS is so thatthe student could know how to prevent it and hoping that the parents can intervene the student social life to stop thisviruses from spreading.Keywords: Relationships of knowledge, attitude and preventive measures, students, HIV/AIDS